Optimization design of stress relief coalbed methane surface well in a high-gas mine - Fu, Junhui; Wen, Guangcai; Zhang, Bichuan; Sun, Haitao; Li, Rifu; Liu, Jiaqi (Frontiers in Earth Science, 2024)
Coalbed methane drainage through surface wells has become increasingly important in high-gas mines. Surface wells are prone to different types of deformations and failures owing to mining-induced effects. In this paper, a displacement and deformation model was established for the overlying strata. Three forms of deformation and failure of the surface well casing was proposed, namely shearing, stretching, and uneven extrusion. Moreover, the mathematical model functions for the S-type shear deformation, delamination tensile deformation, and non-uniform extrusion of the surface well were established. In the Shanxi Coal Group Yue Cheng Mine, coalbed methane drainage at the surface well was conducted on the mining-affected area to achieve good effects. The YCCD-04 well without a local protective device was deformed and damaged, and the dynamic deformation and failure of the surface well was detected using a well imager. The YCCD-02 surface well with a local protective device showed good mining and gas drainage, which verified the effectiveness of the local protective device; the coalbed methane drainage time of this surface well was 35 months, and the cumulative coalbed methane drainage volume extracted was 1.3 × 107 m3. Simultaneously, the problem of gas control in the working face was solved, thereby ensuring the safety of coal mining and achieving good social as well as economic benefits.